Optimization of the MCM-48 Synthesis Method as a Catalyst in the Esterification of Nyamplung Seed Oil into Biodiesel - La Kolo; La Yusran La Kalamu; Nunuk Hariani Soekamto; Paulina Taba; St. Fauziah; Maming Maming; Muhammad Zakir (Automotive Experiences, 2024)
This study was conducted to synthesize MCM-48 based on the surfactants (cetyltrimethylammonium bromide (CTAB) and Triton X-100). The effect of surfactant on MCM-48 was studied in the esterification of nyamplung seed oil. Optimization of the amount of surfactant in the MCM-48 catalyst in the esterification of nyamplung seed oil was carried out by washing and calcination methods. Comparison of GC-MS method and acid-base titration was also studied to determine the activity of the MCM-48 catalyst in the esterification. The results of the Mann Whitney statistical test showed that there was no significant difference (Asymp. Sig. (2-tailed) = 0.967) for the two methods. The effect of the active site on the MCM-48 catalyst activity in the esterification was characterized by FTIR and XRD. The catalyst's activity is significantly influenced by both the percentage transmittance of the silanol active site and the surfactant removal method. The MCM-48 catalyst manufactured by calcination (CTAB-MCM-48/650) performed 12.31% better than the washing approach (CTAB-MCM-48/1w). However, the CTAB-MCM-48 catalyst can be applied to the simultaneous reaction (esterification and transesterification) of the conversion of nyamplung seed oil into biodiesel.